Soft-sensor development for fed-batch bioreactors using support vector regression - Desai, Kiran M.; Badhe, Yogesh P.; Tambe, S. S.; Kulkarni, B. D. (Biochemical Engineering Journal, 2006)
In the present paper, a state-of-the-art machine learning based modeling formalism known as "support vector regression (SVR)", has been introduced for the soft-sensor applications in the fed-batch processes. The SVR method possesses a number of attractive properties such as a strong statistical basis, convergence to the unique global minimum and an improved generalization performance by the approximated function. Also, the structure and parameters of an SVR model can be interpreted in terms of the training data. The efficacy of the SVR formalism for the soft-sensor development task has been demonstrated by considering two simulated bio-processes namely, invertase and streptokinase. Additionally, the performance of the SVR based soft-sensors is rigorously compared with those developed using the multilayer perceptron and radial basis function neural networks. The results presented here clearly indicate that the SVR is an attractive alternative to artificial neural networks for the development of soft-sensors in bioprocesses.
Conference on Atomic Molecular and Optical Physics, Calcutta, INDIA, DEC 13-15, 2005
Keywords: deprotection; Microwave; stannous chloride; tert-butyldimethylsilyl ethers